One-Year Mortality after Traumatic Brain Injury in Liver Cirrhosis Patients—A Ten-Year Population-Based Study. Issue 40 (October 2015) - Cheng, Chieh-Yang; Ho, Chung-Han; Wang, Che-Chuan; Liang, Fu-Wen; Wang, Jhi-Joung; Chio, Chung-Ching; Chang, Chin-Hung; Kuo, Jinn-Rung
Abstract : Abstract: This study investigated the 1-year mortality of patients who underwent brain surgery following traumatic brain injury (TBI) who also had alcoholic and/or nonalcoholic liver cirrhosis (LC) using a nationwide database in Taiwan. A longitudinal cohort study matched by propensity score with age, gender, length of ICU stay, HTN, DM, MI, stroke, HF, renal diseases, and year of TBI diagnosis in TBI patients with alcoholic and/or nonalcoholic LC and TBI patients without LC was conducted using the National Health Insurance Research Database in Taiwan between January 1997 and December 2007. The main outcome studied was 1-year mortality. In total, 7296 subjects (2432 TBI patients with LC and 4864 TBI patients without LC) were enrolled in this study. The main findings were (1) TBI patients with LC had a higher 1-year mortality (52.18% vs 30.61%) and a 1.75-fold increased risk of mortality (95% CI 1.61–1.90) compared with non-LC TBI patients, (2) renal diseases and HF are risk factors, but hypertension could be a protective factor in cirrhotic TBI patients, and (3) TBI patients with non-alcoholic LC and the coexistence of alcoholic and nonalcoholic LC had higher 1-year mortality compared with TBI patients with alcoholic cirrhosis. This study showed that patients with LC who have undergone brain surgery might have higher risk of 1-year mortality than those without LC. In addition, nonalcoholic and the coexistence of alcoholic and nonalcoholic LC show higher 1-year mortality risk than alcoholic in TBI patients with LC, especially in those with comorbidities of hypertension, diabetes mellitus, and stroke.